LITERATURE REVIEW ON RESEARCH ABOUT STUDENTS’ ACHIEVEMENT - Reyes de Rojas, Edith Timofeidina (2014)
Conclusions are drawn from different research pieces which try to identify the factors that condition students’ achievement. We find some that give relevance to school factors as determiners of school achievement. Others have researched the prevalence of the resources and school processes, teachers’ qualities, students’ characteristics (e.g. social and economic background, nutrition) without regarding them as a determinant condition. With reference to teachers’ efficiency, it is stated that teachers’ preparation programs generate meaningful effects in students’ achievement. Others compare the percentage of variance explained by student’s characteristic in relation to the school and teachers. More recent research focuses on the teacher’s efficiency or the teacher’s affective influence as an important factor for students’ achievement.